County to county migration and labour market conditions in Hungary between 1994 and 2002 - Zsombor Cseres-Gergely (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
In this paper I use county to county migration data to estimate the effect of labour market conditions on these flows. A gravity model is estimated on Hungarian NUTS 2 regions for the period between 1994 and 2002. Such results are not available for Hungary so far. Estimated parameters show significant and expected effects of local amenities, distances and labour market conditions. Although the magnitude of the estimated parameters is not small, they are not sizeable enough to compensate for the overall low level of migration.
Keywords: 330; Arbeitsmarktentwicklung; regionale Mobilität - Determinanten; Binnenwanderung; regionaler Arbeitsmarkt; regionale Disparität; Arbeitsmarktindikatoren; ökonomische Faktoren; Lohnhöhe; Arbeitslosenquote; Ungarn